Synthesis of batyl alcohol derived diacylglyceryl ethers possessing omega-3 polyunsaturated fatty acids and active drugs - Svava Dögg Hreinsdóttir 1993- (2019)
The aim of the BS project described in this thesis was the synthesis of four enantiomerically pure diacylglyceryl ether (DAGE) diastereomers derived from batyl alcohol. They were intended as potential prodrugs and were successfully obtained by a four-step chemoenzymatic approach starting from (R)-solketal. All the DAGEs contained a linear saturated C18:0 alkyl chain in the sn-1 position, a non-steroidal anti-inflammatory drug (NSAID), (S)-naproxen or (S)-ibuprofen, in the sn-2 position, and a bioactive polyunsaturated fatty acid (PUFA), EPA or DHA, in the sn-3 position of the glycerol backbone. An immobilized Candida antarctica lipase (CAL) offered excellent regioselectivity in attaching the PUFAs activated as oxime esters exclusively to the end-position of batyl alcohol. Good yields (80%) were obtained for EPA, but, there were some problems encountered in the reaction involving DHA(36%). The coupling of the NSAID molecules was achieved in high to excellent yields(81 – 99%) by the use of EDCI coupling agent in the presence of DMAP serving as a base and catalyst. The identity of all compounds was established and they were fully characterized by 1H and 13C NMR and IR spectroscopy and accurate mass spectrometry analysis. The optical activity was measured for all chiral compounds. Markmið þessa BS verkefnis fól í sér efnasmíðar á fjórum handhverfuhreinum stöðubundnum díasýlglýserýl eterlípíð fjölhverfum batýl alkohóls. Þessar afleiður voru hugsaðar sem möguleg forlyf og tókust efnasmíðarnar vel í fjórum skrefum úr (R)-sólketali sem upphafsefni þar sem lípasa var beitt í einu skrefanna. Allar innihéldu þessar fjórar afleiður línulega mettaða C18:0 alkyl kolvetniskeðju í sn-1 stöðu,verkja- og bólgustillandi lyf, (S)-naproxen eða (S)-íbúprófen, í sn-2 stöðu, og lífvirka fjölómettaða fitusýru, EPA eða DHA, í sn-3 stöðu glyseról hluta sameindarinnar. Kyrrsettur Candida antarctica lípasi (CAL) kom að góðum notum til að innleiða EPA og DHA, virkjuðum sem oxím esterar, alfarið í sn-3 endastöðu batýl alkohólsins. Þannig ...